Pancasila Dalam Berbagai Paradigma di Indonesia - Hariyadi, Bagus - (Universitas Pembangunan Nasional Veteran Yogyakarta, 2024)
The purpose of this paper is to find out the people's economy as a new paradigm and strategy in Indonesia's economic development. The writing of this paper uses the method of literature review (library research). Pancasila experiences inconsistency in continuous development, this is not caused by the weakness of the values contained in it but leads to inconsistencies in its application. In line with the acceptance of the truth of the noble values of Pancasila, the current and enthusiasm for making Pancasila as a paradigm accelerated. Paradigm is a basic assumption and general theoretical assumption so that it is a source of laws, methods, basic principles to solve a problem faced by a nation in the future. From the discussion, it can be concluded that the essence of the position of Pancasila as a development paradigm implies that in all aspects of national development, it must be based on the values contained in the Pancasila precepts. From this paper it can be concluded that Pancasila as a paradigm has a close relationship with the life of society, nation and state. Because Pancasila has a very important role in various fields such as in the fields of law, economy, socio-culture, and also development.